Lappländische Märchen, Volkssagen, Räthsel und Sprichwörter - Poestion, J. C. (Josef Calasanz), 1853-1922, comp. (Wien : C. Gerold, 1886)
Bound with Donner, Otto. Lieder der Lappen. [Helsingfors, 1876]. Mode of access: Internet.